Shrinkage of beech (Fagus sylvatica) and oak (Quercus robur) veneer sheets during the drying process - Castro, A. (2014)
In this paper we studied the retraction of veneer sheets of a diffuse-porous specie (beech) and a ring-porous specie (oak) during the drying process. For each specie we analysed radial and tangential sections, since the differences obtained relate to vessel distribution across the axial or non axial section. Thus, we studied the following parameters: thickness, moisture content, retraction of axial and non axial (radial or tangential) direction. We used 10 beech logs, from which we took 30 samples with a radial cut and 30 samples with a tangential cut. From each log we took 6 veneer sheets. We applied the same procedure to the oak logs. All our veneer sheets were 0,6mm thick. Immediately after cutting, we measured the thickness, moisture content, length and width of each veneer sheet. We measured the same parameters again after the drying process. The two species behaved differently, which we attribute to their distinct anatomical structure, even though both are hardwoods. Variance analyses showed that the species is the main responsible for the variation, and that beech has a higher shrinkage variation. Higher shrinkage results from the tangential cuts, compared to radial cuts.